The Nature of Linguistic Processes Determining the Applicability of Nominalizations Applied to Strings NP-Cop-AP - Uniszewska, Anna (Glottodidactica, 2001)
The article aims at analyzing the principle which determines the acceptability and correctness of nominalizations performed upon sentences of the type: NP-Cop-AP. The discourse was initiated by Chomsky (1972), who demonstrated the fact that the correctness of TNOM>S established by processes taking place in SS, thus suggesting that the analysis of SS might shed light on the nature of the underlying DS processes. This view was lated supported by evidence coming from the analysis of the lexical features of NP and AP, carried out by Postal (1974). Thus discussion was initiated as to the role of 'the lexicalist hypothesis' and iexicalism' in sentence derivation. The author of the article discusses the validity of 'the lexicalist hypothesis', which maintains that lexical features alone can suffice for the explanation of the acceptability of TNOM applied to strings NP-Cop-AP. She claims that the resort to the lexical features needs to be made with respect to, as she calls them, elliptic structures, i. e. structures with shifted designations. In the search for the rule determining the correctness of TN0M, the author considers such principles as: Chomskean observation of its dependence upon the 'rough similarity' between SS and DS (Chomsky 1972), Postal's analysis of agentivity (Postal 1974), the role of the antecedent of the implied subject of the infinitive phrase (whenever it is contained in such structures) and, as she calls it, TNOM-over-TNOM principle. The analysis leads to the conclusion that the acceptability of TNOM CAN be assumed to be determined by the syntactic process. The author names it TNOM" over-TNOM constraint and analyzes it on the selected corpus of English and Polish sentences.